Formulation of Criminal Policy on Sexual Violence Rehabilitation Based on Family Therapy with the Maqasid al-Sharia Principles - Iqbal Kamalludin, Iqbal Kamalludin; Bhanu Prakash Nunna, Bhanu Prakash Nunna (Jurnal Hukum Islam, 2024)
Conventional rehabilitation of victims of sexual violence, which only focuses on physical and psychological recovery has failed to handle the complexity of trauma experienced by victims. Therefore, this study discusses a new approach to the rehabilitation of sexual violence through Family Therapy integrated with the principles of Maqāsid al-Sharī'a. The research method uses normative with a philosophical, conceptual, and statute approaches, which analyzes various legal regulations, doctrines, and principles of Islamic law related to sexual violence and victim rehabilitation. The main data sources include laws, government regulations, fatwas, and court decisions, supported by literature reviews from legal journals, books, and scientific articles. The research findings show that the integration of Family Therapy with the principles of Maqāsid al-Sharī'a is a holistic rehabilitation model, which not only focuses on victim recovery but also pays attention to the roles and dynamics of the family in the rehabilitation process. This model also shows the relevance and practical application of the principles of Maqāsid al-Sharī’a in the recovery efforts of victims of sexual violence, as well as providing important contributions to criminal law policy and practice in the field of mental health and social. This study offers a new inclusive perspective based on humanitarian and religious values in handling victims of sexual violence.